POTENSI PEREKAT TANIN FENOL FORMALDEHIDA KULIT KAYU MANGIUM (Potency of Tannin Formaldehyde Adhesive from Acacia mangium Bark): Gimson Luhan - JHT, Admin (Jurnal Hutan Tropika, 2015)
ABSTRACTBark waste of Acacia mangium could to produce the tannin formaldehyde adhesive that useful as material to the wood working industrial. These material are produced from timber estate of Acacia mangium that widely planted in Sumatera and Kalimantan, and also in the other place, because this species is the fast growing species and relatively easy to grow at the marginal site. Acacia mangium bark was predicted 10% of the logs. The study was aimed to determine the quantity of tannin formaldehyde from Acacia mangium bark that could be developed for the adhesive. The study showed that potency of tannins phenol formaldehyde adhesive namely 435.302,35 ton per year. This materials were able to produce the glue namely 1.691,69 million sheets of plywood approximately. Keywords: Adhesive tannin, bark waste of Acacia mangium, glue